Repeated Stand-Replacing Crown Fires Affect Seed Morphology and Germination in Aleppo pine - Saracino, Antonio; Bellino, Alessandro; Allevato, Emilia; Mingo, Antonio; Conti, Stefano; Rossi, Sergio; Bonanomi, Giuliano; Carputo, Domenico; Mazzoleni, Stefano (Frontiers in Plant Science, 2017)
Post-fire reproductive niche of Aleppo pine (Pinus halepensis) is deeply interlaced with fire products. Indeed, the high pH and low osmotic potentials of ash beds under burnt crowns constitute main constraints to seed germination. In this study, we aim to investigate whether fire recurrence, through the physico-chemical constraints imposed by the ash beds, affects the reproduction ability of P. halepensis at the germination stage. To this aim, Aleppo pine seeds were collected in neighbouring even-aged stands subjected to 0, 1 or 2 fires (namely fire cohorts), and seed morphology and germination performance, in terms of cumulative germination and germination kinetics, were studied under increasing osmotic potentials (from 0.0 to -1.2 MPa) and pH (from 6 to 11). Besides fire history, the role of ontogenetic age of mother plants on seed morphology and germination has been also investigated. Differences in seed morphology among the three cohorts have been highlighted in a multivariate context, with anisotropic enlargement of the seeds produced by pine stands experiencing repeated fires. The patterns of seed germination varied primarily in relation to the fire cohort, with seeds from the pine stand experiencing repeated fires exhibiting enhanced tolerance to pH stress. Conversely, germination performances under osmotic constraints mainly depends on tree ontogenetic stage, with an involvement of fire history especially in the timing of seed germination. Our results suggest that, at least in the short term, fire recurrence does not constrain the reproduction ability of Aleppo pine. These results stimulate new research branches to elucidate the mechanisms behind these responses to recurrent fires.